An exploratory study on the teaching and learning of TOEIC reading comprehension skills at EQuest Academy = Nghiên cứu thăm dò về việc dạy và học phần đọc hiểu TOEIC tại EQuest Academy .M.A Thesis Linguistics: 60 14 01 11 - Phạm, Đức Long (University of Languages and International Studies, 2017)
46 p. + CD-ROM + tóm tắt